The International Implementation of Multisystemic Therapy - Schoenwald, Sonja K. (2008)
The purpose of this article is to consider, through the lenses of theory and research on technology transfer and the adoption and implementation of innovation, the international transport of evidence-based psychosocial treatments for youth, using Multisystemic Therapy (MST) as an example. MST is a well-validated family and community-based approach originally developed in the United States to treat serious juvenile offenders. This article describes challenges to MST transport internationally by virtue of the political, legal, economic, and cultural contexts in different nations. Modifications used to address these challenges and facilitate the international implementation of MST are described and pertain to pre-implementation processes, clinical staff, training materials and procedures, and clinical service delivery.